Building the Processes Behind the Product: How Digital Ventures Create Business Processes That Support Their Growth - Tobias Wuttke; Thomas Haskamp; Michael Perscheid; Falk Uebernickel (Business & Information Systems Engineering, 2024)
Abstract Business process management (BPM) is changing in the digital age. As a result, organizations are confronted with new logics that their business processes adhere to: processes are designed to allow for easy adaptability, infrastructure becomes progressively more flexible, and process participants make their own decisions in ambiguous situations. In this context, business process change becomes increasingly important. Digital ventures – key phenomena in the digital age – heavily rely on digital technology and, hence, have the potential to change quickly. Consequently, their business processes need to change at the same speed. While the literature on BPM proposes different types of business process change and acknowledges that digital technology can enable such developments, it remains to be explored which specific characteristics of digital technology facilitate business process change. The study investigates this by drawing on a multiple case study with seven digital ventures. It finds four patterns of business process changes in digital ventures, illustrating digital technology's impact on business processes. The study compares the patterns with existing types of business process change from the literature and discusses differences and similarities, trying to advance the understanding of business process dynamics in the digital age.
Keywords: 330; Business process management; Digital entrepreneurship; Digital ventures